Idiopathic Ophthalmodynia and Idiopathic Rhinalgia: A Prospective Series of 16 New Cases. Issue 10 (21st July 2015) - Pareja, Juan A.; Montojo, Teresa; Guerrero, Ángel L.; Álvarez, Mónica; Porta‐Etessam, Jesús; Cuadrado, María L.
Abstract : Background: Idiopathic ophthalmodynia and idiopathic rhinalgia were described a few years ago. These conditions seem specific pain syndromes with a distinctive location in the eye or in the nose. We aimed to present a new prospective series in order to verify the consistency of these syndromes. Methods: We performed a descriptive study of all patients referred to our regional neurologic clinics from 2010 to 2014 because of facial pain exclusively felt in the eye or in the nose fulfilling the proposed diagnostic criteria for idiopathic ophthalmodynia and idiopathic rhinalgia. Results: There were 9 patients with idiopathic ophthalmodynia and 7 patients with idiopathic rhinalgia, with a clear female preponderance, and a mean age at onset in the fifth decade. The pain was usually moderate and the temporal pattern was generally chronic. Only one patient reported accompaniments (hypersensitivity to the light and to the flow of air in the symptomatic eye). Preventive treatment with amitriptyline, pregabalin, or gabapentin was partially or totally effective. Conclusions: The clinical features of this new series parallels those of the original description, thus indicating that both idiopathic ophthalmodynia and idiopathic rhinalgia have clear‐cut clinical pictures with excellent consistency both inter‐ and intra‐individually.